eCM 2018
DOI: 10.22203/ecm.v036a07
|View full text |Cite
|
Sign up to set email alerts
|

Decellularised tissues obtained by a CO2-philic detergent and supercritical CO2

Abstract: Tissue decellularisation has gained much attention in regenerative medicine as an alternative to synthetic materials. In decellularised tissues, biological cues can be maintained and provide cellular environments still unmet by synthetic materials. Supercritical CO (scCO ) has recently emerged as a promising alternative decellularisation technique to aggressive detergents; in addition, scCO provides innate sterilisation. However, to date, decellularisation with scCO is limited to only a few tissue types with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
1
37
1
1
Order By: Relevance
“…On the other hand; the most significant property of this fluid is that the transport coefficients 1 . The temperature and pressure of the supercritical fluid are higher than its critical point in which liquid and gas phases cannot be distinguished 3 . Particularly, this fluid has a unique property that can be behaved like a liquid-like density and a gas-like diffusivity/viscosity for transportation.…”
Section: Supercritical Fluid Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand; the most significant property of this fluid is that the transport coefficients 1 . The temperature and pressure of the supercritical fluid are higher than its critical point in which liquid and gas phases cannot be distinguished 3 . Particularly, this fluid has a unique property that can be behaved like a liquid-like density and a gas-like diffusivity/viscosity for transportation.…”
Section: Supercritical Fluid Extraction Methodsmentioning
confidence: 99%
“…However, maintaining the complexity of the cell microenvironment causes many difficulties in the use of synthetic scaffolds. Therefore, studies on the extracellular matrix (ECM) are increasing dramatically in all areas of the world 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Detergents have also been shown to reduce levels of beneficial growth factors in some tissue 23 . Moreover, residual surfactants are cytotoxic 24 , yielding detrimental effects on the subsequent recellularization.As an alternative to detergents, supercritical carbon dioxide (scCO 2 ) has been proposed as a safer, non-toxic and non-residual technology to obtain bio-ECMs from multiple tissues, including porcine heart valve, equine tendon, porcine esophagus, bovine cartilage, human skin, porcine aorta, and human amniotic membrane 17,21,[25][26][27][28][29][30] . The vast majority of these studies have revealed no or a very moderate influence of pressurized carbon dioxide on ECM structure and mechanical properties.…”
mentioning
confidence: 99%
“…On human skin, processing with supercritical CO 2 after a hypertonic 1 M NaCl exposure has produced results similar to those with SDS in terms of cellular content removal (DNA level post-treatment <30 ng/mg of dried ECM) [91]. Small fractures reducing global ECM density were detected, but the fibronectin network seems to be unaffected.…”
Section: Physical Approachesmentioning
confidence: 83%
“…To create hypertonic conditions, NaCl is commonly dissolved at 1 M to weaken cell membranes, as reported in the literature and in patented protocols to process fibroblast sheets, fish skin, and human skin [83,86,89]. Hypertonic NaCl also has been used to dissociate epidermis and dermis [90,91]. A hypertonic solution composed of 1 M KI has been used to process mouse skin [87].…”
Section: Chemicalsmentioning
confidence: 99%